IDENTIFIKASI AKTIVITAS PEKERJAAN PEMANCANGAN DENGAN METODE INNER BORING PADA PROYEK PEMBANGUNAN TANGGUL PENGAMAN PANTAI NCICD - Fadilah, Rifdah; Saputra, Pungky Dharma; Siagian, Gian Asnawi (Politeknik Negeri Jakarta, 2025)
Coastal infrastructure development is a strategic initiative to mitigate tidal flooding in North Jakarta. One of the main projects supporting this effort is the construction of a coastal protection embankment under the National Capital Integrated Coastal Development (NCICD) program. This study aims to identify the stages involved in pile driving using the inner boring method for the NCICD Phase A embankment construction. Compared to conventional methods, the inner boring method was selected due to its advantages in minimizing noise, vibration, and environmental pollution. A mixed-method approach was employed, including video analysis of construction methods, project documentation, surveys, and expert validation. The research identified six primary activities in the pile-driving process: sling installation, pile lifting, shifting, and adjusting the drilling point, auger installation, drilling, and excavation disposal. Survey results showed that nearly all respondents fully agreed with the identified sequence of activities, with two exceptions—sling installation (93%) and pile lifting (87%). Expert validation confirmed full (100%) approval of all identified activities. These activities were subsequently structured into a Work Breakdown Structure (WBS) to improve the efficiency and effectiveness of construction operations. The expert validation results indicate that the identified activity sequence can serve as a reference for similar coastal construction projects. This study is expected to contribute to future embankment construction planning by optimizing time, resources, and workplace safety.